2005
DOI: 10.1111/j.1360-0443.2005.01224.x
|View full text |Cite
|
Sign up to set email alerts
|

Measuring alcohol consumption—should the ‘graduated frequency’ approach become the norm in survey research?

Abstract: The GF does not appear to be appropriate for cross-cultural research. It results in over-reporting of frequencies and appears to be too complex to be administered correctly in many countries. The best measure for these purposes appeared to be the QFBS particularly because it captures more effectively the variability of different alcoholic beverages with different ethanol contents and consumption with different vessel sizes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
0
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(72 citation statements)
references
References 28 publications
0
67
0
5
Order By: Relevance
“…However, as it is well known that more specific questions result in higher reported alcohol intake, there could be some disadvantages with using GF or QF measures compared to the beverage-specific intake on each day in a typical week. The GF approach has, for example been criticized as burdensome and difficult for respondents (Gmel et al, 2006) and, hence, this method is probably not suitable …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as it is well known that more specific questions result in higher reported alcohol intake, there could be some disadvantages with using GF or QF measures compared to the beverage-specific intake on each day in a typical week. The GF approach has, for example been criticized as burdensome and difficult for respondents (Gmel et al, 2006) and, hence, this method is probably not suitable …”
Section: Discussionmentioning
confidence: 99%
“…each day of the week). The QF approach has, for example, been criticized because respondents tend to report modal consumption instead of mean consumption (Gmel et al, 2006). Studies have also shown that the QF method generally generates lower estimates of volume, compared with the GF method (Rehm, 1998).…”
Section: Assessing Alcohol Consumption O Ekholm Et Almentioning
confidence: 99%
“…The validity of self-reported alcohol intake in surveys has often been questioned. [30][31][32][33][34][35] Future research studies might solicit alcohol intake information at several time points, asking the specific context and specific reason to drink in each instance. This strategy would increase the report of alcohol use in order to best evaluate the multidimensional way of drinking.…”
Section: Limitationsmentioning
confidence: 99%
“…Each has its own strengths and weaknesses against various criteria such as internal validity (2), the extent of underreporting (3), capacity to measure patterns of hazardous consumption as well as average volume consumed over time (4), ability to assess compliance with national low risk drinking guidelines (5), cost effectiveness (1) and ability to provide beverage specific information (6,7). In this paper we will provide new comparative analyses of data from a large Australian alcohol and other drug use survey regarding what we will refer to here as the "Yesterday" method which involves detailed questions of beverage types and serve sizes of drinks consumed the day before the interview.…”
Section: Introductionmentioning
confidence: 99%